Respuesta :

xy = -36
x + y = 9

[tex]xy = -36[/tex]
[tex]\frac{xy}{x} =\frac{-36}{x}[/tex]
[tex]y = \frac{-36}{x}[/tex]

[tex]x + y = 9[/tex]
[tex]x + \frac{-36}{x} = 9[/tex]
[tex]\frac{x^{2}}{x} + \frac{-36}{x} = 9[/tex]
[tex]\frac{x^{2} - 36}{x} = 9[/tex]
[tex]9x = x^{2} - 36[/tex]
[tex]0 = x^{2} - 9x - 36[/tex]
[tex]x = \frac{-(-9) \± \sqrt{(-9)^{2} - 4(1)(-36)}}{2(1)}[/tex]
[tex]x = \frac{9 \± \sqrt{81 + 144}}{2}[/tex]
[tex]x = \frac{9 \± \sqrt{225}}{2}[/tex]
[tex]x = \frac{9 \± 15}{2}[/tex]
[tex]x = \frac{9 + 15}{2}[/tex]    [tex]or[/tex]    [tex]x = \frac{9 - 15}{2}[/tex]
[tex]x = \frac{24}{2}[/tex]    [tex]or[/tex]    [tex]x = \frac{-6}{2}[/tex]
[tex]x = 12[/tex]    [tex]or[/tex]    [tex]x = -3[/tex]

    x + y = 9       or        x + y = 9
  12 + y = 9      or       -3 + y = 9
- 12      - 12              + 3       + 3
          y = -3         or          y = 12
(x, y) = (12, -3)    or    (x, y) = (-3, 12)

The two numbers that add up to 9 and multiply to -36 are the numbers -3 and 12.